A small-molecule inhibitor of T. gondii motility induces the posttranslational modification of myosin light chain-1 and inhibits myosin motor activity. - Aoife T Heaslip; Jacqueline M Leung; Kimberly L Carey; Federica Catti; David M Warshaw; Nicholas J Westwood; Bryan A Ballif; Gary E Ward (PLoS Pathogens, 2010)
Toxoplasma gondii is an obligate intracellular parasite that enters cells by a process of active penetration. Host cell penetration and parasite motility are driven by a myosin motor complex consisting of four known proteins: TgMyoA, an unconventional Class XIV myosin; TgMLC1, a myosin light chain; and two membrane-associated proteins, TgGAP45 and TgGAP50. Little is known about how the activity of the myosin motor complex is regulated. Here, we show that treatment of parasites with a recently identified small-molecule inhibitor of invasion and motility results in a rapid and irreversible change in the electrophoretic mobility of TgMLC1. While the precise nature of the TgMLC1 modification has not yet been established, it was mapped to the peptide Val46-Arg59. To determine if the TgMLC1 modification is responsible for the motility defect observed in parasites after compound treatment, the activity of myosin motor complexes from control and compound-treated parasites was compared in an in vitro motility assay. TgMyoA motor complexes containing the modified TgMLC1 showed significantly decreased motor activity compared to control complexes. This change in motor activity likely accounts for the motility defects seen in the parasites after compound treatment and provides the first evidence, in any species, that the mechanical activity of Class XIV myosins can be modulated by posttranslational modifications to their associated light chains.